การพัฒนากระบวนการกรองใสสุราแช่ - สยมพร เอี่ยมขำ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The purpose of this research was to investigate traditional alcoholic beverage (surachae) production and to improve the filtration process by using ultrafiltration prior to bottling. Ultrafiltration is a memebrane separation technique with pore size range of 30-1000 angstrom. It is applied to separate molecules that have molecular weight in the range of 1000-500,000 dalton. The ultrafiltration process was investigated for various pore sizes, pressures and temperatures. The results showed that the appropriate molecular weight cut-offs (MWCO) of the used membrane was 100,000 dalton at 2.0 kg/cm [superscript 2] pressure and room temperature, giving the highest flux. Bacillus cereus was screened from the spoilage alcoholic beverage (surachae). It was used to indicate the efficiency of the membrane filtration. The results showed that ultrafiltration can separate microorganisms in the surachae. Permeate of the surachae had 0 cfu/ml, pH 3.54+ - 0.01, total soluble solid of 21.6 + - 0.0 [superscript 0]Brix, alcohol content of 9.66 + - 0.15 %(v/v), total acidity of 1.35 + - 0.00 g/ 100 ml and reducing sugar content of 37.20 + - 0.11 g/l, meeting the standard of community products. Germs free ultrafiltered surachae in bottles was reinoculated with Bacillus cereus . The reinoculated microorganisms were observed to survive in the bottled product poorly.